ORGANIZATIONAL LEADERSHIP MOTIVATIONAL STRATEGIES AS CORRELATES OF LECTURERS’ INSTRUCTIONAL DELIVERY IN SOUTH EAST, NIGERIA - Ogedi , P. O; Ugwokaegbe, Nancy Chidinma (Journal of Continuing and Development Education, 2024)
This study determined the relationship between organizational leadership motivational strategies and lecturers’ instructional delivery in the South East, Nigeria. The study adopted a correlational design. A sample of 403 lecturers drawn from a population of 1009 lecturers selected from nine public universities in the south east Nigeria using multi-stage sampling procedure. The instruments for data collection were Organizational Leadership Motivational Strategies Introduction Questionnaire (OLMOSTRAQ), and Lecturers’ Instructional Delivery Questionnaire (LIDQ) which were all developed by the researchers. The instruments were validated by two from Educational Management Department and one expert from Science Education Department, all from the College of Education, Michael Okpara University of Agriculture, Umudike, Abia State. Cronbach Alpha statistic was used to determine the reliability coefficient of the instruments which yielded a coefficient of 0.765, and 0.928 for of OLMOSTRAQ, and LIDQ respectively. Three research assistants helped in data collection. Out of the 403copies of the two of instruments administered respectively, 321 copies of each of the instruments representing 80% rate of return were well filled by the respondents and used for data analysis. Pearson product moment correlation was used to answer research question 1 and two while research question 3 was answered using Schiffe’s test. Linear regression analysis was used to test the null hypotheses that guided the study at 0.05 level of significance. The findings showed among others that campus shuttle system significantly to a moderate extent relate to lecturers’ instructional delivery; professional development of lecturers significantly to a very high extent relate to lecturers’ instructional delivery and organizational leadership motivational strategies significantly relate to lecturers’ instructional delivery. Based on the findings, it was recommended among others that university authorities should establish different motivational strategies for her lecturers to ensure effective instructional delivery.